Feasibility Study of the Pregnancy Risk Assessment Monitoring System in Iran. - Roghieh Kharaghani; Mohammad Shariati; Masud Yunesian; Afsaneh Keramat; Alireza Moghisi (Tehran University of Medical Sciences, 2014)
A surveillance system helps to detect epidemics and the pattern of the incidence of the problems in the community and is important for evidence based decision making. This study was conducted to determine the feasibility of the Pregnancy Risk Assessment Monitoring System (PRAMS) in Iran.PRAMS feasibility was assessed in a cross-sectional study in the city of Shahriar, located in the west of Tehran in 2013. In this study, 811 women within 2 to 6 months postpartum who had a live or still birth were selected from thyroid screening forms and hospital records through a systematic simple random sampling method. Trained interviewers collected the data via calling mothers from health centers or through home visits. The outcome was tested on the "TELOS" model including technical, economic, legal, operational and schedule feasibility components.Thirty-seven health volunteers collected the data in this study. Many prevalence estimates were comparable with national and Tehran data (technical feasibility). A home based completed questionnaire cost 2.45 and a phone cost 1.89 USD (economic feasibility). The project was consistent with legal requirements (legal feasibility). The participation rate was 92.8% (95%CI: 92.7-95.3) for home visits and 90.9% (95% CI: 87.3-93.6) for the phonemethod. Over 80% of different sections of the questionnaire were completed (operational feasibility). All data collection processes took 35 days (schedule feasibility).The adapted PRAMS could be considered feasible in Iran. Its widespread and periodic implementation can provide valuable maternal and child health information in the country.